Tam Model: What Affects Gen Z Interest in the Use of e-Wallets? - Humairoh, Humairoh; Mohammad Annas (Dinasti Publisher, 2023)
The reason for this study is to determine the variables Perceived ease of use and Perceived usefulness of hobby in using the OVO E-wallet in technology Z. This study is a quantitative look at. The pattern for this look changed into 79 respondents using the Slovin formulation, with a purposive sampling approach. Number one, data collection is acquired by dispensing questionnaires. The evaluation technique used becomes multiple regression analysis using the SPSS model 26 software program. The consequences showed that perceived ease of use had a positive and significant effect on perceived usefulness, perceived ease of use had a positive and significant effect on interest in using e-wallets, perceived usefulness had an impact positive and significant toward the intention to use an e-wallet and perceived usefulness is moderation of perceived ease of use towards the intention to behave e-wallet. The determinant coefficient is 57.2%. The rest is influenced by factors not examined.